Bioluminescence from the bright and dark sides - Kim, Sung-Bae; Furuta, Tadaomi (Frontiers in Chemical Biology, 2024)
Bioluminescence (BL) is an amazing optical readout that has great potential to be utilized in various bioassays and molecular imaging, but also has some unique defects in practical applications. The recent innovative research on BL has enriched the available repertories of the toolbox. While these efforts greatly diversified the users' choices in the applications, the wide choices on the contrary do not promise their successful applications to bioassays. This is mainly due to complexity-driven confusion with the diversity and the lack of accurate knowledge on the advantages and disadvantages of BL. This review is intended to showcase the advantages and disadvantages of BL, and serve as a searchlight to find directions for future studies. We hope that this review provides instant references for readers on BL and leads them to properly understand the "bright" and "dark" sides of BL to narrow down their choices in their applications.